The relationship between neck strength and sports-related concussion in team sports: A systematic review with meta-analysis - Garrett, J. M.; Mastrorocco, M.; Peek, K.; van den Hoek, D. J.; McGuckian, T. B. (Journal of Orthopaedic & Sports Physical Therapy, 2023)
OBJECTIVE: We aimed to quantify the relationship between neck strength and sports-related concussion (SRC) for athletes participating in team sports.